The role of indigenous and local knowledge on climate adaptation for smallholder farmers in Chiredzi, Zimbabwe - Zvobgo, Luckson (Department of Environmental and Geographical Science, 2025)
Increasing smallholder farmers' resilience to the impacts of climate change requires informed decision-making that utilises locally validated information sources, including Indigenous knowledge (IK) and local knowledge (LK). Smallholder farmers across multiple regions of the world rely on IK and LK forecasts for climate decision making. This knowledge provides a rich foundation for locally led adaptation by smallholder farmers because of its contextual embeddedness within microclimatic conditions. Recent peer-reviewed literature on IK and LK in Africa was analysed to assess the role of IK and LK in adaptation in the water sector, showing that adaptation responses with IK and LK had higher evidence of risk reduction, but only 10% of African governments included IK and LK in adaptation planning in their intended Nationally Determined Contributions. A cross-sectional survey was used to establish the role of IK and LK in adaptation for smallholder farmers in the Chiredzi District, Zimbabwe. Data were collected from 210 smallholder farmers between 2021-2022, through face-to-face interviews. The analysis of observed climate data for Chiredzi between 1972-2022 corroborated the survey data. A framework was developed and applied to assess smallholder farmers' vulnerability in relation to their use of IK and LK. The results demonstrate that IK and LK are important in reducing the vulnerability of smallholder farmers by increasing the implementation of crop adaptation responses. These include the use of indigenous, drought-resistant seed crop varieties and using IK and LK weather and seasonal climate forecasts for informed decision making on appropriate crop varieties and timing of planting to reduce crop exposure to climate risk. Farmers using IK and LK forecasts implemented adaptation responses three times more than those relying on other sources of climate forecasts. Twenty-three decision types from the IK and LK forecasts that contributed to on-farm adaptation responses were identified, including crop variety selection (e.g., drought-resistant crops), cropping area management (e.g., water conservation measures), and agricultural calendar planning and management (e.g., zero tillage, dry planting, or irrigation). A further framework was developed and applied to assess the effectiveness of IK- and LK informed adaptation responses. IK and LK adaptation responses showed limited, positive, and promising signs of effectiveness. Eight (44%) of the 18 responses showed high and medium evidence of effectiveness in reducing climate risk by reducing exposure and vulnerability components of climate risk. The IK and LK seasonal forecasts were most reliable for near- term forecasts. These findings led to the development of a conceptual framework that facilitates the inclusion of IK and LK in planned adaptation. This study broadens the understanding of how IK and LK contribute to the adaptation cycle of the global goal on adaptation of the 2015 Paris Agreement, demonstrating the value of IK and LK to the global climate agenda. The findings of this study are important for interventions that target increasing effectiveness of adaptation responses, thereby reducing smallholder farmers' vulnerability and exposure to climate change. Greater recognition of and attention to IK and LK is needed across national climate adaptation planning in Nationally Determined Contributions and National Adaptation Plans for its potential to be realised